SKRINING KECACINGAN PADA KUKU PETERNAK SAPI - Fahmi, Norma Farizah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Soil-Transmitted Helminths (STH) is a parasite caused by intestinal nematode worms transmitted through the soil. Contaminated soil is the cause of transmission of worm eggs from the soil to humans through eggs attached to the feces of nails or hands and into the mouth along with food. Based on the results of the recapitulation in 2014 Jombang District Health Office there were 285 cases of despised infections. The purpose of this study is to find out the presence of Soil-Transmitted Helminths (STH) worm infection in the hooves of cattle farmers in Bragang Village. This research was descriptive qualitative with a cross-sectional approach. The population used is 31 cattle farmers in Begunung Hamlet, Bragang Village. The samples used amounted to 31 hooves samples using the flotation method. The variable used is Soil Transmitted Helminths (STH) worms. This research was conducted in STIKes Ngudia Husada Madura of Microbiology Laboratory. The results of this study showed that farmers were positive for larvae (90.32%) and worms Ascaris lumbricoides (9,67%). The lifestyle of the community was less hygienic and the work was in direct contact with the soil, such as fertile land areas, farmers, farmworkers, and grass growers. The positive figure of worm in the hooves sample of cattle farmers in Bragang Village as much as 100%. Prevention of infection by washing hands cleanly using water and soap after contact with soil, livestock, cages and after defecation, because soap can shed fat and dirt containing germs.